Evaluation of a Zulu translation of the Parents' Evaluation of Developmental Status - Maria van der Merwe; Marlé Cilliers; Celesté Maré; Jeannie van der Linde; Mia le Roux (AOSIS, 2017)
Background: One of the greatest challenges in early communication intervention in South Africa is developing and implementing successful identification strategies in primary health care (PHC). A shortage of trained PHC personnel is one of the barriers to providing adequate health services in South Africa. This dearth of services creates the need to substitute clinician-administered developmental screening tools with parent-administered tools. Aim: To determine the accuracy of the Zulu Parents' Evaluation of Developmental Status (PEDS) in comparison with the outcome of the English PEDS. Setting: The data were collected in a clinical, non-contrived environment at Stanza Bopape Community Health Clinic in Mamelodi, City of Tshwane. Methods: The PEDS is a standardised, parent-completed questionnaire regarding the child's general development. The English PEDS was translated into Zulu by a Zulu linguist. There were 99 potential participants in the study of whom 83 met the necessary prerequisites. Results: Of the participants whose home language is Zulu, 54% preferred the PEDS in English over the PEDS in Zulu. This indicates a skewed preference towards English, with only slight associations between language preference and age, education and home language. Conclusion: The Zulu PEDS displayed high positive and negative correspondences, representative of an accurate translation of the English PEDS. It is recommended that this study should be repeated in a community where the majority are Zulu home language speakers.